NEW LINE 1 WELDING FRAME BODY COMP DALAM PENINGKATAN KINERJA DAN OPTIMALISASI LINE - Afandy, M. (Industrial and Systems Engineering Assessment Journal (INASEA), 2008)
Along with increased consumer demand of motorcycles, PT Astra Honda Motor as the sole manufacturing company as well as the license holder of Honda motorcycle brand, attempt to fulfill consumer demand by increasing production capacity. To be able to increase the amount of planned production capacity, PT Astra Honda Motor, enacted several policies, such as optimization of existing production capacity, investment in new plant area, and cooperate with the sub contractors. One of the working area of PT Astra Honda Motor, which was affected by these policies is to optimization of the production capacity of Line 1 Welding Frame Body Comp. . The research objective was to try to plan the layout, to improve performance and optimization of line. The aim of the Designing and Making a New Line Welding Frame Body Comp is to improve the performance and optimization of existing production line. After the design of the New Line 1 Welding Frame Comp is completed, weekly production capacity is in accordance with the installed production capacity , smoother process and material flow and increased performance resulted due to the achievement of the operator workstation being more secure and comfortable